Knowledge and attitude of reproductive age group (15-49) women towards Ethiopian current abortion law and associated factors in Bahir Dar city, Ethiopia - Getasew Mulat Bantie; Amare Alamirew Aynie; Mihret kassa Assefa; Ayele Semachew Kasa; Tigabu Birhan Kassa; Gebiyaw Wudie Tsegaye (BMC, 2020)
Abstract Background Unsafe abortion accounts for nearly 60% of all gynecologic admissions and almost 30% of all obstetric and gynecologic admissions. Studies on abortion in Ethiopia have given less attention to women's perceptions and experiences of abortion laws. Although the 2005 revised abortion law allows women to access safe abortion services, still unsafe abortion is one of the leading causes of pregnancy-related deaths. Therefore, the current study aimed to assess women's knowledge and attitude towards the Ethiopian current abortion law in Bahir Dar City Administration. Methods A community-based cross-sectional study using a systematic random sampling technique was carried out among 403 randomly selected reproductive age women using a pre-tested structured questionnaire in Bahir Dar City Administration from May to June /2017. Data were entered into Epi data version 3.1 and analyzed using SPSS version 21.0 software. Logistic regression was done to identify the possible factors associated with women's knowledge and attitude towards the Ethiopian current abortion law. Results Three hundred eighty-six respondents partook with a response rate of 95.7%. The study showed that 43% had good knowledge and 38% had a favorable attitude towards the Ethiopian current abortion law. Women's in the age group of 25-29 years (AOR = 2.7, 95% CI: 1.02, 6.9), partner's educational status of primary (AOR = 2.9, 95% CI: 1.19, 7.08), secondary (AOR = 5.5, 95% CI: 2.09, 14.4) and college and above (AOR = 8.2, 95% CI: 2.3, 28.6) were significantly associated with good knowledge of the Ethiopian current abortion law. While partner's educational status; college and above (AOR = 6.15, 95% CI: 1.87, 20.22) was significantly associated with the favorable attitude towards the Ethiopian current abortion law. Conclusions 43% of respondents had good knowledge and 38% had a favorable attitude towards the Ethiopian current abortion law. Forty-nine respondents had a history of abortion of which, 8 occurred through induction. Woman's age and partner's education determine the status of knowledge while merely; the partner's educational status of college and above was significantly associated with the attitude towards Ethiopian current abortion law, respectively.